Fair Trade in a Digital Environment from the Urban Perspective in Merida, Yucatan, Mexico - Hernández Islas, Mireya Noemi; Godínez Molina, Gina Estefanía; Cruz Chim, Annel Jhoana (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To know the familiarity of the inhabitants of the urban areas of Mérida, Yucatán, Mexico, to buy by digital means, fruit and vegetables from fair trade, and to have an appropriate marketing channel with the new generations.MATERIAL AND METHOD: A research with a quantitative approach and exploratory scope, as well as a cross-sectional design, was determined. Due to the type of data used, the paradigm to be used is quantitative, through the collection and analysis of measurable information.RESULTS: The population studied gave indications of being technologically literate, that is, the majority incorporate the use of the Internet and Information and Communication Technologies (ICT) in their daily lives, being Generation Z and Millennials, the ones that have the most knowledge of these.CONCLUSIONS: Digital consumption is no longer under discussion, it is increasingly common that these consumer behaviors become inherent to the lifestyle, that´s why it is important to incorporate this activity into the fair trade of agricultural products.
Keywords: Electronic commerce; Faair trade; Consumer behavior; Digital environment; Digital media.